KABHANTI WUNA MEDIA KOMUNIKASI TRADIOSONAL DAN TANTANGANNYA DI ERA GLOBALISASI - Hardiman Hardiman; Ardianto Ardianto (Institut Agama Islam Negeri (IAIN) Manado, 2016)
Abtract.On the ethnic communities of Muna at Southeast Sulawesi be known their Wuna kabhanti arts performance. Kabhanti arts performance was not only an expression of the culture, but at the same time were aneducationalan media, communication and entertainment. In the field of education, perfomances of kabhanti contributed in the establishment and embedded of noble character. It communicative language make kabhanti’s performance arts could be used as a medium of communication, especially as a medium for conveying messages morals, ethics, education, and development. Therefore, on the verge of extinction, continuity and conservation of arts performance of kabhanti needs to be continuously conducted as one of the local culture and local wisdom of ethnic communities of Muna ar Southeast Sulawesi.Key Word: Kabhanti Wuna, Medium of Communication, Traditional,Globalization Abtrak.Dalam masyarakat etnis Muna di Sulawesi Tenggara dikenal adanya seni pertunjukan kabhanti Wuna.Seni pertujukan kabhanti tidak hanya merupakan suatu ekspresi kebudayaan, tetapi sekaligus media pendidikan, komunikasi, dan hiburan.Dalam bidang pendidkan, pertunjukan kabhanti membantu dalam pembentukan dan penanaman watak yang luhur.Bahasanya yang komunikatif menjadikan seni pertunjukan kabhanti dapat dipakai sebagai sarana komunikasi, khususnya sebagai media penyampaian pesan-pesan moral, etika, pendidikan, dan pembangunan.Oleh karena itu, di ambang kepunahannya, pemertahanan dan pelestarian seni pertunjukan kabhanti ini perlu dilakukan teus-menerus sebagai salah satu budaya lokal nusantara dan kearifan lokal etnis Muna di Sulawesi Tenggara.Kata kunci: Kabhanti Wuna, Media Komunikasi, Tradiosonal, Globalisasi